Changes in mitral regurgitation following acute myocardial infarction: early and long-term follow-up. (14th October 2021) - Sharma, H; Yuan, M; Shakeel, I; Radhakrishnan, A; Brown, S; May, J; Zia, N; O'Connor, K; Hothi, S S; Myerson, S G; Nadir, M A; Steeds, R P
Abstract: Background: Mitral regurgitation (MR) is commonly observed following acute myocardial infarction (MI). Localised left ventricular (LV) remodelling in the region of papillary muscles together with impaired myocardial contractility promote MR. There is a paucity of long-term follow-up studies to determine whether the severity of MR observed post-MI, changes with time. Purpose: This study retrospectively followed up patients with MR detected following acute MI (AMI) to investigate changes in MR severity with time and assess for pre-discharge predictors of MR regression or progression. Methods: Clinical records of 1000 patients admitted with AMI between 2016 and 2017 to a single centre were retrospectively interrogated. One hundred and nine patients met the inclusion criteria of MR on pre-discharge transthoracic echocardiography (TTE) and follow-up TTE scans. Echocardiographic parameters were investigated to determine predictors of progression or regression at follow-up. Patients were divided according to those who had early follow-up TTE (within 1-year) and late follow-up TTE (beyond 1-year). Results: Early follow-up TTE was performed in 73 patients at a median of 6 (IQR 3–9) months. Patients had a mean age of 69±13 years and were predominantly male 50/73 (68%). At baseline, relative MR severities were: 49/73 (67%) mild MR, 23/73 (32%) moderate MR and 1 (1%) severe MR. At follow-up, MR had completely resolved in 18/73 (23%) patients, while 39/73 (53%) had mild MR, 15/73 (21%) moderate MR and 1 (1%) severe MR. Compared to patients with no resolution of MR, those with completel resolution were younger (mean age 62±16 vs 72±11 years; p=0.015) but there were no other significant differences between the groups. Resolution at early follow-up did not significantly influence long-term mortality rates. Late follow-up TTE was performed in 69 patients at a median 2.4 (IQR 2–3.2) years. Pre-discharge, 49/69 (71%) patients had mild MR and 20/69 (29%) moderate MR. At follow-up, MR had completely resolved in 18/69 (26%), and amongst patients with persistent MR, proportion of severities were: 37/69 (54%) mild MR, 11/69 (16%) moderate MR and 3/69 (4%) severe MR. Patients with progression of mild MR were more likely to have lower left ventricular ejection fraction (LVEF: 47±15 vs 57±12%; p=0.010) and greater indexed left ventricular end-systolic volume (LVESVi: 37±23 vs 25±14 ml/m 2 ; p<0.001) on pre-discharge TTE. Resolution of MR at late follow-up was associated with a reduction in long-term mortality [deaths: 2/55 (3%) vs 3/14 (21%); p=0.022] at a mean follow-up of 4.2 years from MI. Conclusion: MR observed following AMI completely resolved in approximately one-quarter of patients at 6-month and 2-year follow-up. Progression of mild MR at long-term follow-up appears to be associated with increased mortality and is predicted by lower LVEF and greater LVESVi pre-discharge. Funding Acknowledgement: Type of funding sources: None.